Correlation of VEGF expression with prognostic factors of breast carcinoma (Bangladesh Journal of Medical Science, 2019)
Background: Breast carcinoma is the most common malignant tumour and leading cause of cancer death among women worldwide. VEGF being a powerful mediator of angiogenesis, plays a major role in local growth as well as metastasis of many solid tumours including breast carcinoma.Objective: This study aimed to evaluate the significance of VEGF expression in breast cancer and its correlation with prognostic parameters. Materials and methods: This study was conducted over a period of one year (February 2015 to January 2016). VEGF expression was evaluated in 57 histologically diagnosed cases of breast carcinoma with known ER and HER-2/neu status.Result: Among 57 cases 52(91.2%) were positive for VEGF. Positive ER expression was seen in 39 cases which is 64.8% of total cases. 54% of the total cases were positive for HER-2/neu. VEGF expression was positively correlated (P value